Prototyping real-time multitasking systems. - Junaid, Amjad. (University of Ottawa (Canada), 1990)
Real-time multitasking systems represent a class of complex, dedicated computer systems whose designs require careful analysis and involve several tradeoffs. Two of the main phases in the development of such systems are defining the required functional characteristics of the system, and then translating these requirements into a working design. A substantial amount of progress has been made in systematizing the functional specification phase but the more traditional ad-hoc approach is still largely used in the design phase of these systems. The purpose of this thesis is to show the feasibility of applying development tools and imposing a structured methodology to this design phase of the development process. It is assumed that such a systematic approach to the design phase will reduce development time and cost and result in more reliable and efficient systems. To meet these objectives, this thesis describes the main factors that must be considered in the design of multitasking systems. It also introduces a design prototyping tool that has been specifically designed to gather application specific information pertaining to these factors. Finally, a methodology is proposed that uses this tool to assist in formulating a final design.
Keywords: Engineering, Electronics and Electrical.